Polyphosphate binds with high affinity to exosite II of thrombin - Mutch, N.J. (2009)
BACKGROUND: Polyphosphate (a linear polymer of inorganic phosphate) is secreted from platelet dense granules and we recently showed that it accelerates factor V activation by thrombin. OBJECTIVE: To examine the interaction of polyphosphate with thrombin. METHODS AND RESULTS: Thrombin, but not prothrombin, altered the electrophoretic migration of polyphosphate in gel mobility assays. Thrombin binding to polyphosphate was influenced by ionic strength and was evident even in plasma. Two positively charged exosites on thrombin mediate its interactions with other proteins and accessory molecules: exosite I (mainly with thrombin substrates), and exosite II (mainly with certain anionic polymers). Free thrombin, thrombin in complex with hirudin’s C-terminal dodecapeptide, and gamma-thrombin all bound polyphosphate similarly, excluding exosite I involvement. Mutations within exosite II, but not exosite I, the Na(+)-binding site or hydrophobic pocket, weakened thrombin binding to polyphosphate as revealed by NaCl-dependence. Surface plasmon resonance demonstrated tight interaction of polyphosphate with thrombin (K(d) ~5 nM) but reduced interaction with a thrombin exosite II mutant. Certain glycosaminoglycans, including heparin, only partially competed with polyphosphate for binding to thrombin, and polyphosphate did not reduce heparin-catalyzed inactivation of thrombin by antithrombin. CONCLUSION: Polyphosphate interacts with thrombin’s exosite II at a site that partially overlaps, but is not identical to, the heparin binding site. Polyphosphate interactions with thrombin may be physiologically relevant, since polyphosphate concentrations achievable following platelet activation are far above the ~5 nM K(d) for the polyphosphate-thrombin interaction.